Phosphatidylserine-microbubble targeting-activated microglia/macrophage in inflammation combined with ultrasound for breaking through the blood–brain barrier - Ranran Zhao; Jie Jiang; Huiwen Li; Min Chen; Renfa Liu; Sujuan Sun; De Ma; Xiaolong Liang; Shumin Wang (Journal of Neuroinflammation, 2018)
Abstract Background and purpose Inflammatory reaction plays a crucial role in cerebral ischemia reperfusion (IR) injury. It has been shown that activated microglia long-term existed in cerebral ischemia and induced second injury. Therefore, we hypothesize that prepared phosphatidylserine (PS)-modified microbubbles (PS-MBs) combined with ultrasound-targeted microbubble destruction (UTMD) can safely open the blood–brain barrier (BBB) and target activated microglia for inflammatory area in the later stage of ischemia reperfusion. Methods To verify our hypothesis, rat model of IR was established, then the change of activated microglia/macrophage (M/M) and permeability of BBB at 1, 7, 14, and 21 days could be clearly observed post IR. And the activated M/M still can be observed during the whole experiment. Results The Evans blue extravasation of BBB gradually declined from day 1 to day 21. Compared to the control group, microbubbles containing PS were taken up more by activated M/M (approximately twofold) both in vitro and in vivo. Conclusions PS-MBs combined with ultrasound (US) exposure could safely open BBB, and the resulting PS nanoparticles (PS-NPs) could further target activated M/M in the neuroinflammation.